Decree no. 336/2016 on the tax dispute settlement application form issued in accordance with the provision of law 79/2016 = قرار وزاري رقم 336 لسنة 2016 بشأن نموذج طلب إنهاء المنازعة الضريبية وفقا لأحكام القانون رقم 79 لسنة 2016 - Egypt. Ministry of Finance. The Egyptian Customs Authority (2025)
Ministry of finance Decree No. 336 of the year 2016 On the Tax Dispute Settlement Application Form Issued in Accordance with the Provisions of Law No. 79 of the year 2016 وزارة المالية قرار رقم 336 لسنة 2016 بشأن نموذج طلب إنهاء المنازعة الضريبية وفقاً لأحكام القانون رقم 79 لسنة 2016